Translation and Validation of FLACC scale in Urdu Language - Aatika Khalid Omer, Shoaib Waqas, Muhammad Tariq, Hassan Bin Akram, Muhammad Waqas Mughul, Somia Faisal, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To translate and validate FLACC scale in Urdu language Methods: At the Ghurki Trust and Teaching Hospital (GTTH), cross-cultural linguistic validation research using non-probability convenient sampling was carried out for 7 months, from July 2021 to January 2022. Two native Urdu speakers with sound English language understanding, one from medical background and second from educational background translated the English FLACC scale. Two English-certified linguists who did not have access to the English version subsequently reverse-translated these two versions into English. These Urdu translations and back translations were critically analyzed and reviewed by a committee of paediatric physical therapists and paediatric clinical practitioners, and a final Urdu version was prepared. After approval of the final translation, this Urdu FLACC scale was applied in the post-operative paediatric population to assess its validity and reliability. After 2 hours, bilingual subjects were administered the English version, while others were again assessed with the Urdu FLACC scale to check linguistic interchangeability and test-retest reliability. Informed consent was taken and documented as well; this study was approved by the Ethical Review Board of Lahore Medical and Dental College, Lahore, Punjab, Pakistan. SPSS version 26 was used for data entry and as well as analysis. Inter-rater reliability was evaluated by using Intraclass correlation coefficients, which determines the strength of association and measure of chance-corrected agreement. The construct validity of the FLACC tool was evaluated by using ABC of content validation and content Validity Index Calculation. Results: The mean age and standard deviation of patients was 5.333+1.5599. The ABC of Content Validation Index, which yielded an average proportion of 0.97. The Cronbach’s alpha of translated FLACC scale is 0.701 when applied on population. Intraclass correlation coefficient ranged from 0.319-0.701 with acceptable reliability. Conclusion: The FLACC scale's translated Urdu version shows good validity and reliability. Key terms: Consolability, Pain, Preverbal population, Validity, Reliability, neonatal ICU